2004
DOI: 10.2355/isijinternational.44.74
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preoxidation of Titania-Ferrous Ore on the Ore Structure and Reduction Behavior

Abstract: The paper examined an effect of preoxidation of titania-ferrous ore (New Zealand ironsand) on the ore structure and reduction by carbon monoxide.The major phase in ironsand is titanomagnetite, Fe 3 O 4 -Fe 2 TiO 4 solid solution, with spinel cubic structure. In the non-isothermal preoxidation titanomagnetite was oxidized to cubic maghemite and then transformed to rhombohedral titanohematite, Fe 2 O 3 -FeTiO 3 solid solution. Isothermal preoxidation of the ironsand at 1 273 K transformed titanomagnetite to tita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 8 publications
2
56
0
Order By: Relevance
“…Previous studies show that coal-based direct reduction followed by magnetic separation is the most effective method to achieve titanium and iron separation from TTM ore. [8][9][10][11][12][13][14][15] The process involves the following steps: First, TTM ore of the proper size, coal, and additives are mixed together. Second, the mixture is placed in a crucible and roasted at a high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies show that coal-based direct reduction followed by magnetic separation is the most effective method to achieve titanium and iron separation from TTM ore. [8][9][10][11][12][13][14][15] The process involves the following steps: First, TTM ore of the proper size, coal, and additives are mixed together. Second, the mixture is placed in a crucible and roasted at a high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…They found that pre-oxidation accelerated the reduction process by destroying the crystal lattice of the VTM and causing the formation of pores in the particles. Similarly, Park 10) concluded that pre-oxidation of the iron sand increased its reducibility because of the structural transformation of spinel cubic TTM to rhombohedral TTH. However, different conclusion was obtained by Liu,11) the main phases of the VTM oxidized at 900°C for 6 min were Fe 9 TiO 15 and Fe 2 O 3 .…”
Section: Relationship Between the Phases Structure Mgo Migration Anmentioning
confidence: 99%
“…The basis for the experiments rest on reported investigations of many alternative routes for the production of TiN from ilmenite (FeO · TiO 2 ). [36][37][38][39][40][41][42][43] The production of grain refiners directly from ilmenite ore eliminates the need of mixing of different powders; it is economically attractive and can easily be scaled up to industrial scale in a DRI-type of installation.…”
Section: Development Of New Ces-based Grain Refinersmentioning
confidence: 99%